Efficient photoreduction of diluted CO2 using lattice-strained Ni1−xSe nanoflowers. (October 2022) - Liang, Shujie; Zeng, Gongchang; Zhong, Xiaohui; Deng, Hong; Zhong, Zuqi; Lin, Zhang; Huang, Jianlin
Abstract: Photoreduction of diluted CO2 is an effective strategy for the sustainable and environmentally friendly development of energy. In this study, lattice strain in NiSe is modulated through the control of the Ni concentration for the photoreduction of diluted CO2 . Refined XRD data and the results of the Williamson–Hall analysis indicate that the lattice strain is induced by lattice distortion caused by an absence of Ni atoms in the crystal lattice. In pure CO2, the cumulative CO yield and selectivity of Ni1−x Se nanoflowers reached approximately 19.39 µmol and 90.7 % in 3 h, respectively. For lower CO2 concentrations of 0.1 and 0.05 atm, the CO selectivity of Ni1−x Se was approximately 72.7 % and 61.7 %, respectively. On characterization of the synthesized nanoflowers, we deduced that the lattice-strained Ni1−x Se exhibited a favorable electronic band structure that improved the separation efficiency of the photogenerated carriers. DFT calculations results revealed that the lattice strain significantly facilitated the adsorption and activation of CO2, which resulted in highly efficient CO2 photoreduction. This study provides an effective strategy for the design and synthesis of high-performance catalysts based on the modification of their crystal structures. Graphical Abstract: Lattice-strained Ni1−x Se nanoflowers are prepared by adjusting the solvothermal temperature, which are applied for CO2 photoreduction and afford 61.7–92.4% CO selectivity within 5–100% CO2 concentration. ga1 Highlights: Lattice-strained Ni1−x Se nanoflowers were synthesized using the solvothermal method. Lattice strain could be adjusted by modulating the Ni concentration. Lattice-strained catalysts were utilized for the photoreduction of diluted CO2 . Ni1−x Se exhibited effective photocatalytic conversion of diluted CO2 to CO.